Implementasi Pembelajaran Intrakurikuler Projek Penguatan Profil Pelajar Pancasila di UPT SD Negeri 066050 Medan Denai - Anggun R. Gurning; Desi R.S Situmorang; Hotma U. Sitanggang; Ignasius Aritonang; Roi R. Manik; Tiara Agustin (Journal Innovation In Education, 2024)
This study is based on the reality that students still do not understand the diversity of culture, ethnicity and religion in Indonesia. Because the school environment generally consists of several relatively similar tribes and cultures, as well as the environment around the students' homes, which lacks cultural and ethnic diversity. With a relatively similar cultural and ethnic background around students, students are less familiar with the diversity in Indonesia, so it is feared that they will not have tolerance for differences, as the proverb says "if you don't know, you don't love". Because of this, this study aims to improve students' understanding of the diversity of culture, ethnicity and religion in Indonesia, so that students know how to behave when they encounter diversity. In this study, we used a descriptive qualitative method, with observation, planning, implementation, and activity results techniques. The focus of this study is class VA at UPT SD Negeri 066050 Medan Denai which is one of the driving schools and has implemented the Merdeka Curriculum, with a total of 23 students. Based on the research results, the school has implemented P5 intracurricular learning in schools since 3 years ago. Through these activities, students can be formed according to the six dimensions contained in the Pancasila Student Profile Strengthening Project.